2014
DOI: 10.4236/jct.2014.51012
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Neoadjuvant Therapy Compared to the “Resection First” Approach for Patients with Borderline Resectable Pancreatic Adenocarcinoma

Abstract: Background: Survival for patients with pancreatic adenocarcinoma continues to be poor. Patients with pancreatic adenocarcinoma that is deemed borderline resectable have imaging that shows disease involvement of the portal vein and/or superior mesenteric vein that is amenable to reconstruction or abutment (≤180 degrees) of the superior mesenteric artery. The best initial treatment for patients with borderline resectable pancreatic adenocarcinoma has yet to be determined. Proponents of neoadjuvant therapy purpor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 43 publications
(28 reference statements)
1
0
0
Order By: Relevance
“…6,7,9 Margins achieved were better (ie more R0 resections) with the robotic approach, but while this seems consistent with what others have reported, 10 there is room for improvement; neoadjuvant therapy was not uniformly applied, reflecting our bias. 11 We have previously reported that our patients had fewer complications than reported within NSQIP, and this group of patients looked like those previously reported. 3 Complications were relatively uncommon, occurring in fewer than 1 of 5 patients, and were generally not serious, with only 1 of 3 patients with a complication having a complication of grade 3 or greater; this means that less than 1 in 15 patients had a complication of grade 3 or greater.…”
Section: Discussionsupporting
confidence: 84%
“…6,7,9 Margins achieved were better (ie more R0 resections) with the robotic approach, but while this seems consistent with what others have reported, 10 there is room for improvement; neoadjuvant therapy was not uniformly applied, reflecting our bias. 11 We have previously reported that our patients had fewer complications than reported within NSQIP, and this group of patients looked like those previously reported. 3 Complications were relatively uncommon, occurring in fewer than 1 of 5 patients, and were generally not serious, with only 1 of 3 patients with a complication having a complication of grade 3 or greater; this means that less than 1 in 15 patients had a complication of grade 3 or greater.…”
Section: Discussionsupporting
confidence: 84%